2011
DOI: 10.1111/j.1551-2916.2011.04926.x
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroxylation and Rehydroxylation Mechanisms in Fired Clay Ceramic: A TGMS and DRIFTS Investigation

Abstract: Selected instrumental techniques [dilatometry, thermogravimetry – mass spectrometry (TG‐MS), and variable temperature – diffuse reflectance infrared Fourier transform spectroscopy (VT‐DRIFTS)] have been used to investigate the role of moisture in the rehydroxylation reaction which causes expansion and mass gain in fired clay ceramics. The temperature range over which adsorbed water molecules and structural hydroxyl groups are desorbed from fired clay ceramic as it is reheated, and the nature of the structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…The effect of heat on the FTIR spectrum of clay minerals has been extensively explored (Farmer, 1974;Shoval et al, 1991Shoval et al, , 2011Berna et al, 2007;Savage et al, 2008;Clegg et al, 2012). It has been shown that reversible and irreversible structural changes with heat occur in clay minerals, producing significant spectral changes that allow identification of heating temperature.…”
Section: Background To the Study Of Mud Bricks In Conflagration Eventmentioning
confidence: 99%
“…The effect of heat on the FTIR spectrum of clay minerals has been extensively explored (Farmer, 1974;Shoval et al, 1991Shoval et al, , 2011Berna et al, 2007;Savage et al, 2008;Clegg et al, 2012). It has been shown that reversible and irreversible structural changes with heat occur in clay minerals, producing significant spectral changes that allow identification of heating temperature.…”
Section: Background To the Study Of Mud Bricks In Conflagration Eventmentioning
confidence: 99%
“…It causes a small increase in mass and appears to continue indefinitely. Wilson, Hall et al [1][2][3][4][5][6][7][8] established that the kinetics of this reaction depends on the quartic (fourth) root of the elapsed time (time) 1/4 ; and suggested that the RHX process may be used as an "internal clock" to establish the age of archeological ceramics; that is, the time elapsed since the ceramic pottery was fired. Figure 1 shows the notation and illustrates the RHX dating method.…”
Section: Introductionmentioning
confidence: 99%
“…1 In addition, Clegg et al demonstrated that the water lost from archeological samples during reheating was replaced after exposure to humid air. 2 The water vapor present in the atmosphere is sufficient to drive the rehydration/rehydroxylation process, which can be divided into the initial gain of physically bonded (i.e., adsorbed) water and the reaction of water with meta-clays in the sample. It is has been observed that both processes proceed concurrently at early times, thus comprising "Stage I" behavior.…”
Section: Introductionmentioning
confidence: 99%
“…(1)] as well as the time 1/n empirical model of rehydration/rehydroxylation mass gain [Eq. (2)]. The previous report by the authors examined the effects of temperature and humidity fluctuations.…”
Section: Introductionmentioning
confidence: 99%